An estimation of the X/Q value for the first Philippine Nuclear Power Plant (PNPP-1) - Marcelo, Veronica J.
Atmospheric transport and dispersion of gaseous effluents in routine releases from the first Philippine Nuclear Power Plant (PNPP-1) were determined using the XOQDOQ computer code. This code is a computer program which calculated average relative effluent concentrations (X/Q's) and average relative disposition values (D/Q's) at locations specified by the user, and at standard radial distances and segments for downwind sectors for routine plant releases. The input data utilized for the estimation of atmospheric transport and dispersion are based on the information gathered from the Final Safety Analysis Report (FSAR) and the Environmental Report (ER) for the first Philippine Nuclear Power Plant.